Photosynthetic Bioelectronic Sensors for Touch Perception, UV‐Detection, and Nanopower Generation: Toward Self‐Powered E‐Skins. Issue 39 (12th August 2018) - Ravi, Sai Kishore; Wu, Tingfeng; Udayagiri, Vishnu Saran; Vu, Xuan Minh; Wang, Yanan; Jones, Michael R.; Tan, Swee Ching
Abstract: Energy self‐sufficiency is an inspirational design feature of biological systems that fulfills sensory functions. Plants such as the "touch‐me‐not" and "Venus flytrap" not only sustain life by photosynthesis, but also execute specialized sensory responses to touch. Photosynthesis enables these organisms to sustainably harvest and expend energy, powering their sensory abilities. Photosynthesis therefore provides a promising model for self‐powered sensory devices like electronic skins (e‐skins). While the natural sensory abilities of human skin have been emulated in man‐made materials for advanced prosthetics and soft‐robotics, no previous e‐skin has incorporated phototransduction and photosensory functions that could extend the sensory abilities of human skin. A proof‐of‐concept bioelectronic device integrated with natural photosynthetic pigment‐proteins is presented that shows the ability to sense not only touch stimuli (down to 3000 Pa), but also low‐intensity ultraviolet radiation (down to 0.01 mW cm ‐2 ) and generate an electrical power of ≈260 nW cm ‐2 . The scalability of this device is demonstrated through the fabrication of flexible, multipixel, bioelectronic sensors capable of touch registration and tracking. The polysensory abilities, energy self‐sufficiency, and additional nanopower generation exhibited by this bioelectronic system make it particularly promising for applications like smart e‐skins and wearable sensors, where the photogenerated power can enable remote data transmission. Abstract : Toward a self‐powered photosynthetic electronic skin, a bioelectronic sensor is developed that makes use of natural photosynthetic pigment‐protein complexes to sustain a variety of functions, including touch‐perception, UV‐detection and nanopower generation. Proof‐of‐concept multipixel devices are shown to be capable of touch registration and tracking, and applications such as UV‐sensing e‐skins are considered.